ANALYSIS OF FACTORS CAUSED FOR DELAYING CONSTRUCTION ROAD REHABILITATION AND MAINTENANCE IN KEJAYAN PURWOSARI’S (LINK 197) PROJECT DUE TO COVID-19 PANDEMIC - Ramadhani, Ardhi; Muhammadun, Haris; Oetomo, Wateno (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
Implementation of Construction Projects that run within a limited time must be removed from the factors that cause project delays to run optimally and appropriately. This study aims to analyze the factors causing delays in road rehabilitation and maintenance in Kejayan Purwosari (Link 197) construction projects due to the Covid-19 pandemic. The study population consist of 80 people and the number of research samples is the total population. The data collection technique is done by distributing questionnaires. Techniques for analyzing research data using Partial Least Square (PLS). The results of the study prove that the factors of Manpower, Materials and Equipment have no significant effect on Project Delay. Meanwhile, the factors of Construction Method, Relationship and Time and Control have a significant effect on Project Delay.